2013
DOI: 10.1002/anie.201301676
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Chiral Oxathiozinone Scaffolds: Efficient Synthesis of Hindered Enantiopure Sulfinamides and Sulfinyl Ketimines

Abstract: Ist das S‐O? Die im Titel bezeichneten Molekülgerüste verfügen über eine hoch aktive und ausreichend differenzierte S‐O‐Bindung für die effiziente Synthese enantiomerenreiner Sulfinamide. Die beschriebene Methode ist praktisch und umweltverträglich und könnte als Grundlage für ein ökonomisches kommerzielles Verfahren zur Herstellung sperriger Sulfinamide dienen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Finally, we also tried the ring opening of 7 bA using 2‐mesitylmagnesium bromide, but in this case, we were able to isolate only the corresponding symmetrical sulfoxide, even when the reaction was carried out at −78 °C or using a two‐fold excess of 7 bA . This last result was not completely unexpected, since the symmetrical sulfoxide was obtained also by Senanayake as the major product when using the more sterically hindered 1,3,5‐triisopropylphenylmagnesium bromide [9] …”
Section: Methodsmentioning
confidence: 73%
See 3 more Smart Citations
“…Finally, we also tried the ring opening of 7 bA using 2‐mesitylmagnesium bromide, but in this case, we were able to isolate only the corresponding symmetrical sulfoxide, even when the reaction was carried out at −78 °C or using a two‐fold excess of 7 bA . This last result was not completely unexpected, since the symmetrical sulfoxide was obtained also by Senanayake as the major product when using the more sterically hindered 1,3,5‐triisopropylphenylmagnesium bromide [9] …”
Section: Methodsmentioning
confidence: 73%
“…With the desired chiral precursors 6 in our hands, we studied their conversion into the corresponding oxathiazine 2-oxide scaffolds 7 and their efficiency as stereoselective sulfinyl transfer agents in the preparation of enantiomerically enriched tBSA, using the same protocols recently reported by Han and Senanayake (Scheme 3). [9,10] Scaffolds 7 were prepared by reaction with thionyl chloride and pyridine in THF at À 15 °C, in good to high yields. Except for 7 aA, which can be isolated and purified by flash-chromatography on silica as a stable white solid, all other oxathiazine 2-oxides are unstable and easily hydrolyze back to the precursors 6 if prolonged reaction times are used, as well as during the work-up stage and during purification by flash-chromatography on silica.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…But these conditions are harsh, and there is the additional drawback that large amounts of hazardous NH 2 Li/NH 3 must be handled and disposed of. During the course of our work, Senanayake reported a phenol‐based tert ‐butanesulfinylating agent that is able to smoothly give the sulfinamide intermediate 42. We found that the addition of LiHMDS to ( R S )‐DAG‐ tert ‐butanesulfinate ester 2 R S in THF at 0 °C, followed by treatment with methanol and silica, gave the desired enantiopure ( R S )‐ tert ‐butanesulfinamide ( 17 R S ) in 92 % yield (Scheme ).…”
Section: Resultsmentioning
confidence: 96%